Effects of the unit cell topology on the compression properties of porous Co-Cr scaffolds fabricated via selective laser melting. Issue 1 (16th January 2017) - Han, Changjun; Yan, Chunze; Wen, Shifeng; Xu, Tian; Li, Shuai; Liu, Jie; Wei, Qingsong; Shi, Yusheng
Abstract : Purpose: Selective laser melting (SLM) is an additive manufacturing process suitable for fabricating metal porous scaffolds. The unit cell topology is a significant factor that determines the mechanical property of porous scaffolds. Therefore, the purpose of this paper is to evaluate the effects of unit cell topology on the compression properties of porous Cobalt–chromium (Co-Cr) scaffolds fabricated by SLM using finite element (FE) and experimental measurement methods. Design/methodology/approach: The Co-Cr alloy porous scaffolds constructed in four different topologies, i.e. cubic close packed (CCP), face-centered cubic (FCC), body-centered cubic (BCC) and spherical hollow cubic (SHC), were designed and fabricated via SLM process. FE simulations and compression tests were performed to evaluate the effects of unit cell topology on the compression properties of SLM-processed porous scaffolds. Findings: The Mises stress predicted by FE simulations showed that different unit cell topologies resulted in distinct stress distributions on the bearing struts of scaffolds, whereas the unit cell size directly determined the stress value. Comparisons on the stress results for four topologies showed that the FCC unit cell has the minimum stress concentration due to its inclined bearing struts and horizontal arms. Simulations and experiments both indicated that the compression modulus and strengths of FCC, BCC, SHC, CCP scaffolds with the same cell size presented in a descending order. These distinct compression behaviors were correlated with the corresponding mechanics response on bearing struts. Two failure mechanisms, cracking and collapse, were found through the results of compression tests, and the influence of topological designs on the failure was analyzed and discussed. Finally, the cell initial response of the SLM-processed Co-Cr scaffold was tested through the in vitro cell culture experiment. Originality/value: A focus and concern on the compression properties of SLM-processed porous scaffolds was presented from a new perspective of unit cell topology. It provides some new knowledge to the structure optimization of porous scaffolds for load-bearing bone implants.